2018
DOI: 10.1371/journal.pgen.1007547
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of lipoprotein QseG with sensor kinase QseE in the periplasm controls the phosphorylation state of the two-component system QseE/QseF in Escherichia coli

Abstract: Histidine kinase QseE and response regulator QseF compose a two-component system in Enterobacteriaceae. In Escherichia coli K-12 QseF activates transcription of glmY and of rpoE from Sigma 54-dependent promoters by binding to upstream activating sequences. Small RNA GlmY and RpoE (Sigma 24) are important regulators of cell envelope homeostasis. In pathogenic Enterobacteriaceae QseE/QseF are required for virulence. In enterohemorrhagic E. coli QseE was reported to sense the host hormone epinephrine and to regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 67 publications
1
24
0
Order By: Relevance
“…Complementation of the rapZ + strain with the plasmid encoding wild‐type QseF resulted in intermediate glmY’‐lacZ levels, whereas ~2‐fold lower activities were measured in the presence of the QseF‐D56A variant, which mimics non‐phosphorylated QseF (Fig C). The latter activities reflect the residual ability of non‐phosphorylated QseF to activate glmY expression when overproduced (Göpel & Görke, ). High glmY expression levels were obtained in the presence of the QseF‐D56E variant, which mimics phosphorylated QseF (Fig C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Complementation of the rapZ + strain with the plasmid encoding wild‐type QseF resulted in intermediate glmY’‐lacZ levels, whereas ~2‐fold lower activities were measured in the presence of the QseF‐D56A variant, which mimics non‐phosphorylated QseF (Fig C). The latter activities reflect the residual ability of non‐phosphorylated QseF to activate glmY expression when overproduced (Göpel & Görke, ). High glmY expression levels were obtained in the presence of the QseF‐D56E variant, which mimics phosphorylated QseF (Fig C).…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, both domains of RapZ and proper oligomerization are required for undisturbed binding of QseE/QseF suggesting that tetrameric RapZ activates this TCS (Fig EV1). Recently, we have shown that QseE/QseF employ the lipoprotein QseG as third essential component (Göpel & Görke, ). Kinase QseE requires interaction with QseG in the periplasm for activity suggesting that a quaternary signaling complex involving RapZ must form to obtain a fully activated TCS (Fig ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this system, energy involvement is more complex than with standard EPBs, in that instead of being an ATP‐binding protein, QseF needs to be phosphorylated by QseE in complex with outer membrane sensor QseG to activate its cognate promoters. However, we witness also an energy‐dependent recycling process in that QseE must be dephosphorylated by a second activity of the QseE protein (phosphatase) to start another round of control (Gopel and Gorke, ).…”
Section: An Open List Of Basic Cellular Maxwell's Demonsmentioning
confidence: 99%
“…This mechanism may be in particular important when GlmY levels are low, e.g. when the QseE/QseG/QseF three-component system, which controls glmY transcription, is in the OFF state [34,35]. Under these conditions, accumulation of GlmZ* may limit further processing of full-length GlmZ thereby maintaining a robust GlmS basal level.…”
Section: Expression Of the Srna Chimeras Mimicking Glmz* Augments Glmmentioning
confidence: 99%